Communities Of Practice, Foucault And Actor‐Network Therory - Fox, Stephen (Journal of Management Studies, 2000)
The paper discusses some of the main contributions to the theory of communities of practice (COP theory), especially as it relates to organizational learning. The paper does not attempt a full overview but concentrates on the notion of power relations. Early COP theory was formulated as part of situated learning theory, and promised to work on issues of social context and unequal power relations. Foucault’s work and actor‐network theory (ANT) is introduced and forms the basis of a constructive critique of COP theory. The paper argues that COP theory and ANT can enrich each other and together make a stronger contribution to our understanding of organizational learning. Specifically, these perspectives question the value in viewing organizations as formal, canonical entities as far as learning and change are concerned.